2012
DOI: 10.1007/s00425-012-1638-6
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis BPG2: a phytochrome-regulated gene whose protein product binds to plastid ribosomal RNAs

Abstract: BPG2 (Brz-insensitive pale green 2) is a dark-repressible and light-inducible gene that is required for the greening process in Arabidopsis. Light pulse experiments suggested that light-regulated gene expression of BPG2 is mediated by phytochrome. The T-DNA insertion mutant bpg2-2 exhibited a reduced level of chlorophyll and carotenoid pigmentation in the plastids. Measurements of time resolved chlorophyll fluorescence and of fluorescence emission at 77 K indicated defective photosystem II and altered photosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Loss of BPG2 function causes a yellow leaf phenotype and abnormal 16S and 23S rRNA accumulation. BPG2 was found to bind to 16S and 23S rRNA (Komatsu et al, 2010;Kim et al, 2012). Thus, it would be interesting to analyze the embryogenesis phenotype of the atnoa1 atbpg2 double mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of BPG2 function causes a yellow leaf phenotype and abnormal 16S and 23S rRNA accumulation. BPG2 was found to bind to 16S and 23S rRNA (Komatsu et al, 2010;Kim et al, 2012). Thus, it would be interesting to analyze the embryogenesis phenotype of the atnoa1 atbpg2 double mutant.…”
Section: Discussionmentioning
confidence: 99%
“…To corroborate the finding that maturation of 16S rRNA was specifically affected and to identify the steps where the maturation pathway was perturbed, we performed Northern blot analysis using a specific probe against mature 16S rRNA ( Figure 3a). As positive controls for small chloroplast subunit defects we included two known chloroplast 30S assembly factor mutants rif1 (resistant to inhibition by fosmidomycin) (Flores-P erez et al, 2008) and bpg2 (Brz-insensitive-pale green 2) (Kim et al, 2012). While in the WT, mature 16S rRNA was the most abundant rRNA, atrsgA-i, rif1 and bpg2 mutants showed accumulation of 17S rRNA, a precursor of 16S rRNA ( Figure 3d) (Fristedt et al, 2014).…”
Section: Atrsga Is Involved In the Maturation Of 30s Ribosomes In Chlmentioning
confidence: 99%
“…Previous studies reported that BPG2, as a YqeH-type GTPase, participates in chloroplast rRNA maturation 31 32 . To determine whether the lack of YL1 is responsible for the phenotypes of yl1-1 , we introduced the full-length open reading frame of YL1 to the yl1-1 mutant under the control of the 35S promoter.…”
Section: Resultsmentioning
confidence: 98%